Sistem Informasi Manajemen Usaha E-Commerce Dropshipper Berbasis Web (Studi Kasus : Fakultas Sains dan Teknologi Universitas Labuhanbatu) - Zakiyul Albab (Universitas Labuhanbatu, 2021)
Dropshipper is a profession of sellers without providing products and also hassle in packaging and shipping services, where this sales system is considered to be very easy and practical, without having to take a lot of costs and places to store traded goods. However, there are also many shortcomings in the dropship business, one of which is the lack of control over the goods purchased by the buyer and the large number of orders can make sales records irregular.The making of this information system aims to find out how the online dropshipper business works, design an e-commerce dropshipper business management application, and can provide information about what is needed in the online dropshipper business and build an information system that can be used to facilitate the performance of dropshipper sellers in business management. Making this management information system can easily help dropship entrepreneurs to manage their businesses well.